Synthesis and characterization of novel oxime derivatives - Arslan, Taner; Keskin, Serhat; Demirayak, Şeref (Bentham Science Publ Ltd, 2016)
Background: The synthesis of effective drugs are very important for the scientist. The various biological effects of the thiazole, oxime and ether functional groups are well known properties by the drug developers. So we have synthesised new molecules which contains three of them on the same molecules. Methods: The acetophenone derivatives have been used for synthesis new oximes. The synthetic pathway includes mainly four steps. sl. alpha-Bromination of acetophenone derivatives, s2. Synthesis of thiazole ring using brominated acetophenones, s3. Synthesis of ethers using synthesised thiazole, s4. Synthesis of oximes. Results: The synthesised molecules characterised using IR, I H-NMR, 13C-NMR and elementel analysis methods. Conclusion: The new oximes which include thiazole and ether groups have been synthesised using acetophenone derivatives.
WOS: 000391709300008
Keywords: Thiazole; Oxime; Ether